THE ROLE OF LEARNING FACILITATORS IN ORGANIZING LIFE SKILLS EDUCATION PROGRAMS AT SKB UNGARAN - Taufik Aldian Hidayat; Tri Suminar (SOSIOEDUKASI, 2025)
This study aims to describe the role of learning facilitators in organizing life skills education programs (PKH) at SKB Ungaran and identify supporting and inhibiting factors in its implementation. This study uses a descriptive qualitative approach with data collection techniques through structured interviews, participatory observation, and documentation. The results of the study show that learning facilitators have four main roles, namely as an identifier of community needs, program designers, activity implementers, and evaluators of program results. In the implementation of the program, learning facilitators play the role of informers, facilitators, and motivators who play an active role in guiding and motivating learning residents. Supporting factors for the success of the program include the availability of adequate facilities and infrastructure, funding support from the local government, and the enthusiasm of learning residents. Meanwhile, inhibiting factors include limited learning competencies and high workloads. Based on the results of the research, it was concluded that the success of the life skills education program at SKB Ungaran was greatly influenced by the professionalism of the learning facilitators, institutional support, and synergy between related parties. Therefore, it is recommended that SKB Ungaran improve the development of learning competencies and provide post-program assistance effectively to improve the quality of the implementation of life skills education programs and realize an increase in people's independence and quality of life.